1990
DOI: 10.1103/physrevb.41.9024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfur vacancies on the crystallographic and spin-rotation transitions of iron sulfide

Abstract: Sulfur-deficient iron sulfide, Fe, 04S, has been studied in comparison with FeS by Mossbauer spectroscopy at various temperatures ranging from 82 to 600 K. It is found that the 4 at. % sulfur vacancy makes the crystallographic a transition from the (NiAs, MnP) structure to a superstructure take place abruptly within 5 K with the superstructure stable up to 410 K. The spin-rotation transition of Fe&~S takes place at 455 K, which is higher by 63 K than that of FeS. The Neel temperature is not affected appreciabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Similar independence of the Morin and a transitions was reported by Thiel and van den Berg [5] using Mössbauer measurements for Fe 0.996 S, though they found that T M was lower by 28 K than T a in contrast to the other results [6][7][8].…”
supporting
confidence: 85%
“…Similar independence of the Morin and a transitions was reported by Thiel and van den Berg [5] using Mössbauer measurements for Fe 0.996 S, though they found that T M was lower by 28 K than T a in contrast to the other results [6][7][8].…”
supporting
confidence: 85%
“…g 0 and g 1 represent the absolute values of g factors for the ground and the first excited levels of the 57 Fe nucleus, respectively. μN stands for the nuclear magneton and H is the magnetic hyperfine field [5]. Therefore, from Eq.…”
Section: Resultsmentioning
confidence: 99%
“…1 [5]. The quartz tube with two narrow necks was first filled with the desired amount of sulfur and then covered by one layer of titanium and iron powder each.…”
Section: Methodsmentioning
confidence: 99%
“…On heating, the Low Temperature Phase (LTP), the superstructure (P62c) derived from the NiAs-type structure, transforms at around 400 K into the High Temperature Phase (HTP), a transitional phase which can be described by the MnP (Pnma) orthorhombic structure [2][3][4]. The transition is reversible and of the first order, then both phases coexist within a temperature interval which, depending on stoichiometry, goes from a few degrees to around 200 K. Both phases are antiferromagnetic with iron atoms located at unique crystallographic sites.…”
Section: Introductionmentioning
confidence: 99%